Karakteristik Fisik Sensoris dan Kimia Cookies dengan Penambahan Puree Pisang Masak Varietas Kepok dan Edible Flower Rosela (Hibiscus sabdariffa) serta Telang (Clitoria ternatea) - Dian Nur Fauziyah (Fakultas Teknologi Pertanian, 2024)
Bananas are classified as climacteric fruits that are still undergoing a ripening process when they are harvested. The use of bananas processed into puree and mixed into dry cake products such as cookies as an effort to diversify local food and can help extend their shelf life. In addition, the addition of edible flowers in making cookies aims to be an application of edible flowers that can be an alternative in innovation, especially for taste. This study was conducted to obtain a selected banana cookie formula based on an effectiveness test and to determine the physical, chemical and sensory characteristics of cookies. The stages of this study were making cookies, then physical analysis was carried out including color and texture, hedonic sensory analysis (preference) and chemical analysis including proximate analysis and also crude fiber content. Based on the results of the ANOVA statistical analysis, the use of banana puree with different concentrations had a significant effect on the physical value of texture and hedonic (color and overall values). Cookies with the addition of 24% banana puree are selected banana cookies with sensory properties of all parameters, namely liked, physical properties of texture parameters of 361.6 - 410.27 g / mm (rosella flowers), 365.6 - 406 g / mm (butterfly pea flowers); 369.47 - 444.6 g / mm (rosella and butterfly pea flowers) and brightness values (L *) of 37.76 - 51.26 and yellowness values (b *) of 42.20 - 67.73, then from the chemical properties of selected banana cookies, respectively, water content of 4.13% - 6.12%; ash content of 0.95% - 1.01%; fat content of 20.51% - 21.59%, protein content of 11.00% - 11.89%; carbohydrate content is 59.54% - 62.51% and crude fiber content is 0.09% - 0.24%.
Reaploud Repository February 2026_Hasyim
Keywords: Kepok Banana; Cookies; Local Food.